Probing the Structure and Evolution of Anode Materials in Thermal Batteries - Azad, Atia (Cranfield University, 2020)
High-temperature thermal batteries use lithium-silicon alloys as the anode material. Li13Si4, Li7Si3 and Li12Si7 alloys are studied to determine if phase transitions occur or if the alloys become amorphous between room temperature and 500◦C (the typical operating temperature of thermal batteries). These alloys are synthesised by reacting lithium metal and silicon powder at elevated temperature inside an evacuated quartz ampoule. The samples’ structural changes are investigated at elevated temperatures using in situ powder neutron diffraction. This is carried out on the Polaris diffractometer at ISIS facility, Rutherford Appleton Laboratory, UK. The results of the neutron scattering experiment seem to imply that the alloys do not become amorphous at 500◦C and no phases transitions occur in the temperature range. Further work is required to determine if phase transitions occur below room temperature. The work so far has presented a simple method of synthesising these alloys and gives information on the lack of phase transitions between room temperature and 500◦C.
Keywords: 'DSDS20 Poster'; 'DSDS20'; 'Thermal battery'; 'Lithium-silicon'; 'Anode material'; 'Metals and Alloy Materials'